Culture and Use of Mesenchymal Stromal Cells in Phase I and II Clinical Trials - Bourin Philippe; Sensebé Luc; Planat-Bénard Valérie; Roncalli Jérôme; Bura-Rivière Alessandra; Casteilla Louis (Stem Cells International)
Present in numerous tissues, mesenchymal stem cells/multipotent stromal cells (MSCs) can differentiate into different cell types from a mesoderm origin. Their potential has been extended to pluripotency, by their possibility of differentiating into tissues and cells of nonmesodermic origin. Through the release of cytokines, growth factors and biologically active molecules, MSCs exert important paracrine effects during tissue repair and inflammation. Moreover, MSCs have immunosuppressive properties related to non-HLA restricted immunosuppressive capacities. All these features lead to an increasing range of possible applications of MSCs, from treating immunological diseases to tissue and organ repair, that should be tested in phase I and II clinical trials. The most widely used MSCs are cultured from bone marrow or adipose tissue. For clinical trial implementation, BM MSCs and ADSCs should be produced according to Good Manufacturing Practices. Safety remains the major concern and must be ensured during culture and validated with relevant controls. We describe some applications of MSCs in clinical trials.